Changes in transcription pattern lead to a marked decrease in COX, CS and SQR activity after the developmental point of the 22(nd) gestational week - Kolarova, H; Krizova, J; Hulkova, M; Hansikova, H; Hulkova, H; Smid, V; Zeman, J; Honzik, T; Tesarova, M (Physiological research, 2018)
Tissue differentiation and proliferation throughout fetal development interconnect with changes in the oxidative phosphorylation system (OXPHOS) on the cellular level. Reevaluation of the expression data revealed a significant increase in COX4 and MTATP6 liver transcription levels after the 22(nd) gestational week (GW) which inspired us to characterize its functional impact. Specific activities of cytochrome c oxidase (COX), citrate synthase (CS), succinate-coenzyme Q reductase (SQR) and mtDNA determined by spectrophotometry and RT-PCR were studied in a set of 25 liver and 18 skeletal muscle samples at 13(th) to 29(th) GW. Additionally, liver hematopoiesis (LH) was surveyed by light microscopy. The mtDNA content positively correlated with the gestational age only in the liver. The activities of COX, CS and SQR in both liver and muscle isolated mitochondria significantly decreased after the 22(nd) GW in comparison with earlier GW. A continuous decline of LH, not correlating with the documented OXPHOS-specific activities, was observed from the 14(th) to the 24(th) GW indicating their exclusive reflection of liver tissue processes. Two apparently contradictory processes of increasing mtDNA transcription and decreasing OXPHOS-specific activities seem to be indispensable for rapid postnatal adaptation to high energy demands. The inadequate capacity of mitochondrial energy production may be an important factor in the mortality of children born before the critical developmental point of the 22(nd) GW.
Keywords: vývoj plodu; Liver; játra; Electron Transport Complex IV; těhotenství; Muscle, Skeletal; Transcription, Genetic; genetická transkripce; Fetal Development; Citrate (si)-Synthase; ženské pohlaví; Humans; Pregnancy; respirační komplex II; kosterní svaly; citrátsynthasa; Electron Transport Complex II; Female; respirační komplex IV; lidé